Gazebos and trellises : authentic details for design and restoration - Harrison, Peter Joel. 4 0 16; 5 (New York : Wiley, 1999)
Contains illustrations of gazebos and trellises based on examples found primarily in New England and states along the eastern coast, covering belvederes, garden temples, pavilions, tea houses, and other garden structures and supports.
Includes bibliographical references.
Adult;Adult
Keywords: 2 -- 0; 6; Gazebos.;Trellises.;Gazebos.;Trellises.; 20; 2